Thinning effects on carbon allocation to fine roots in a Quercus ilex forest - López, B C; Sabate, S; Gracia, C A (Tree Physiology, 2003)
The dynamics of the fine root system are relevant to calculations of the carbon balance of the ecosystem, and there is also a need to quantify changes in this component caused by disturbances. Mediterranean forest systems have historically been coppiced to obtain charcoal. As a result of the resprouting capacity of holm oaks (Quercus ilex L.), these forests present more than 50% of their biomass below ground (stump + roots > 1 cm in diameter), but the effects of thinning on the fine root system are unknown. Fine root biomass, production, mortality and longevity were studied in a control and a thinned Mediterranean holm oak forest by minirhizotron methodology. Observations of fine roots started 2 years after thinning and continued for almost 3 years. Extraction of 80% of the former basal area of the forest greatly affected carbon allocation patterns. Biomass increased by more than 100%, production increased by 76%, mortality increased by 32% and longevity decreased by around 2 weeks. The greatest differences between treatments were associated with differences in growth during autumn months in the top 40 cm of soil, particularly between 10 and 20 cm depth.
10.1093/treephys/23.17.1217
Keywords: biomass; longevity; mortality; production

Fine-root longevity of Quercus ilex - López, B; Sabate, S; Gracia, C A (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern

Modelling the responses to climate change of a Mediterranean forest managed at different thinning intensities: Effects on growth and water fluxes - Gracia, C A; Sabate, S; Tello, E (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
This study explores the effect of various climatic change scenarios over a 50 year period on plots managed at a range of thinning intensities. In order to determine how management practises can modify the effect of climatic change on Mediterranean Forests we integrated field experiments and the results of the GOTILWA model so as to take into account both water fluxes and forest structure interactions. The results show that the positive effects of atmospheric CO2 fertilisation, causing an increase in WUE, counteract with the negative effects of both temperature increase and rainfall decrease. Thinning might attenuate the effects of adverse conditions by reducing both leaf respiratory costs and the foliage turnover rate.
Keywords: climate change; mediterranean forest; Modelling

Nutrient content in Quercus ilex canopies: seasonal and spatial variation within a catchment - Sabate, S; Sala, Anna; Gracia, C A (Plant and Soil, 1995)
Spatial and temporal changes in canopy nutrient content were studied in 1988 and 1989 in a Mediterranean Quercus ilex ssp. ilex L. forest in north-eastern Spain. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a small catchment (ridge top at 975 m and valley bottom at 700 m). Deeper soils resulted in significantly higher N and P concentrations, and N content on a leaf area basis at the valley bottom site. In contrast, K concentration in leaves was significantly higher at the ridge top site, where soil K concentration was also higher. At both sites, N and P content on a leaf area basis was highest at the top of the canopy, where leaf area is highest. N resorption efficiency decreased from top to bottom of the canopy. Results suggested a minor role of shaded leaves as nutrient storage sites. Lower P resorption efficiency was found at the ridge top site. Seasonal changes of P and N concentration on a leaf area basis suggest P replenishment, and to a lesser degree N, during periods of lower growth activity due to low temperatures, but coinciding with higher water availability (autumn-early spring period). Thus, N and P resorption from the remaining foliage in the canopy took place, and to a larger degree at the valley bottom site, coinciding with a slightly higher leaf area index and productivity at this site.
Keywords: Canopy; nutrient content and dynamics; nutrient resorption; Quercus ilex

ASPECTOS ECOFISIOLOGICOS RELACIONADOS CON LA PRODUCCION DE LOS ENCINARES MEDITERRANEOS - Gracia, C A; Sala, A; Sabate, S (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The productivity of Quercus ilex forests is low in relation to other tree species. Waterand nutrients are often the most important limiting factors. Nevertheless the ecophysiological traits of this specie could help to explain the observed patterns of productivity. Leaf area index of european evergreen-oak forests is rather constant with values about 5. The energetic cost of formation and maintenance of the leaves of Quercus ilex accounts for more than 50 per cent of total carbon fixed by the trees. The resproutig ability of evergreen oaks could explain the high density and low mean diameter of these populations. The high proportion of living tissues in this type of structuni increases the respiration costs of the stems and branches. As a consequence, an important fraction of carhon fixed by leaves is used to maintain the structure of the community which contribute to explain the low observed net primary production of Quercus ilex forests
Keywords: ecophysiology; L.A.I.; productivity; Quercus ilex

Preliminary results of a fertilization-irrigation experiment in a Quercus ilex L. forest in relation to leaves and twigs characteristics - Sabate, S; Calvet, S; Gracia, C A (Plant Ecology, 1992)
A multifactorial ANOVA experiment was designed for a Quercus ilex forest in the Prades mountains in Tarragona (NE Spain). The purpose of this study was to clarify the relative importance of water, ni- trogen and phosphorus as factors controlling primary production. Eight plots comprising all possible combinations of the three factors (including a control) were laid out in three replicate blocks. Fertilizers were applied to the appropriate treatments in March 1989 with a dosage of 125 kg of P/ha and 250 kg N/ha. Irrigation was applied with a rate of 20 mm per week during the warm season. To evaluate the effects on canopy structure we measured specific leaf weight (rag/cruZ), average leaf weight (rag), average twig height and average twig length. These variables were selected as they are the most likely to manifest changes over short time periods following changes in environmental conditions. The values of these parameters before initial treatments (autumn 1988) and after treatments (summer 1990) were analyzed. The results obtained show that water and nitrogen have a greater effect than phosphorus on tree canopy structure, at least during initial development.
Keywords: fertilization experiment; Irrigation experiment; leaves and twigs characteristics